Diuretic Activity of the Hydroalcoholic Extracts of Rhizomes and Leaves of Artemisia Abyssinica Sch. Bip. ex A. Rich: In Silico and in Vivo Study - Abdu, Nebiyu; Alebachew, Yonatan (Scripta Medica, 2024)
Background/Aim: In addition to their adverse effects and drug-drug interactions, the affordability and availability of diuretics are a major problem in developing countries. Consequently, the majority of communities in developing nations utilise traditional medicine as an alternative or a combination therapy with a clinically approved diuretic regimen. The present study aimed to investigate the in vivo and in silico diuretic properties of the 80 % methanol extracts of the rhizomes and leaves of Artemisia abyssinica, an indigenous traditional diuretic medicinal plant of Ethiopia. Methods: Acute oral toxicity tests of 80 % methanol rhizome and leaf extracts of the plant were conducted in mice. For the diuretic test, six treatment groups were administered 100, 200 and 400 mg/kg doses of rhizome and leaf extracts of the plant. The negative and positive control groups were treated with distilled water (2 mL/100 g) and furosemide (10 mg/kg), respectively. Cumulative urine volume, diuretic action, diuretic activity and saluretic index were then determined. In addition, virtual screening and molecular docking study of the compounds of the genus Artemisia were done.Results: The rhizome and leaf extracts of A abyssinica were found safe at a dose of 2000 mg/kg. Moreover, both extracts showed a significant diuretic action (p < 0.05). However, compared to the standard drug furosemide, the extracts had lower diuretic activity. The rhizome extract increased electrolyte excretion at all doses; particularly at the 200 and 400 mg/kg doses, it exhibited a profound natriuretic, chloruretic and kaliuretic effect with the concentration of 109 and 110 mmol/L for Na+, 93 and 106 mmol/L for Cl‒ and  79 and 86 mmol/L for K+, respectively. These suggested inhibition of Na+-K+-2Cl‒ cotransporter as the potential mechanism of action of the extracts. Accordingly, virtual screening and a molecular docking analysis of the compounds of the genus Artemisia revealed that a few of them displayed a strong binding interaction with the cation-chloride cotransporter NKCC1 (PDB: 7S1Y), further indicating the cation-chloride cotransporter as a diuretic target of the constituents of the plant.Conclusion: The current study supports the traditional claim of the plant for diuresis and recommends further isolation of the active constituents.